A Gamified Approach to Participatory Modelling of Water System Risks - Coletti, Alex; De Nicola, Antonio; Vicoli, Giordano; Villani, Maria Luisa (Critical Information Infrastructures Security, 2018)
Modelling risks related to critical infrastructures requires integrated and multi disciplinary competencies of experts, stakeholders, and users who are often located in different places and have limited time to be involved in a strenuous knowledge elicitation project. In this context we propose a gamified and participatory modelling approach to boost engagement of people involved in risk assessment related to critical infrastructures. The approach is supported by a risk management system based on the ICE-CREAM framework, including the CREAM (CREAtivity Machine) software for computational creativity and the ICE (Innovation through Collaborative Environment) mobile app developed for iOS. Insights on risk assessment of water systems are also discussed.